2006
DOI: 10.1161/01.str.0000225929.96190.b3
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genomic Loci Influencing Plasma Homocysteine Levels

Abstract: Background and Purpose-Genetic factors that influence interindividual variation in levels of plasma homocysteine, a risk factor for vascular disease, are not fully understood. We performed linkage analyses to identify genomic regions that influence homocysteine levels in blacks and non-Hispanic whites. Methods-Subjects (nϭ2283) belonged to hypertensive sibships and included 1319 blacks (63Ϯ10 years, 70% women) and 964 non-Hispanic whites (61Ϯ7 years, 57% women). Fasting plasma homocysteine was measured by high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…IPA is a knowledge-based discovery tool and the largest curated database of previously published findings on mammalian biology. [30][31][32] The CRP gene was located under the linkage signal for CRP on chromosome 1q21-23, but we did not find a linkage signal for the region on chromsome 4q28 that harbors the genes encoding fibrinogene peptides (FGA, FGB, and FGG). Seven genes (FCER1G, SELP, SERPINC1, ITGB3, GH1, SCARB1, and TCF1) involved in the expression, activation, and degradation of fibrinogen were identified under the linkage signals for plasma fibrinogen (Table 4).…”
Section: Potential Candidate Genes In the Linked Regionscontrasting
confidence: 62%
“…IPA is a knowledge-based discovery tool and the largest curated database of previously published findings on mammalian biology. [30][31][32] The CRP gene was located under the linkage signal for CRP on chromosome 1q21-23, but we did not find a linkage signal for the region on chromsome 4q28 that harbors the genes encoding fibrinogene peptides (FGA, FGB, and FGG). Seven genes (FCER1G, SELP, SERPINC1, ITGB3, GH1, SCARB1, and TCF1) involved in the expression, activation, and degradation of fibrinogen were identified under the linkage signals for plasma fibrinogen (Table 4).…”
Section: Potential Candidate Genes In the Linked Regionscontrasting
confidence: 62%
“…rs117569851, in the promoter of CARM1, was associated with plasma homocysteine levels in a Chinese population, specifically urbanites in the north of China with above-normal mean level of homocysteine. Regardless of different races of the sample groups between our study and that of Kullo et al, 26 the consistent results strongly imply that CARM1 contributes to the regulation of homocysteine. However, our result did not overlap with the 2 genomewide linkage studies in Europeans that identified nicotinamide N-methyltransferase and ras-related nuclear protein as genetic determinants of plasma homocysteine levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, our result did not overlap with the 2 genomewide linkage studies in Europeans that identified nicotinamide N-methyltransferase and ras-related nuclear protein as genetic determinants of plasma homocysteine levels. 26,34 Higher folate intake in Europeans than in Chinese is likely one of the reasons interpretating the inconsistency between Europeans and Chinese. Elevated activity of intracellular methyltransferases is associated with increased cellular homocysteine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important determinants of plasma hcy are renal function and age (Brattstrom et al 1994). Genetic factors are also important in determining circulating hcy concentration and have been estimated as explaining 20-70% of the variability depending on cohort studied (Bathum et al 2007;Kullo et al 2006;Reed et al 1991). The most consistently identiWed sequence variation shown to inXuence circulating hcy concentration is the 677C-T change (g.677C > T) in the gene for methylenetetrahydrofolate reductase (MTHFR OMIM#607093) (Frosst et al 1995).…”
Section: Introductionmentioning
confidence: 99%